2019
DOI: 10.1001/jamanetworkopen.2019.10465
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childhood History of Parental Incarceration and Juvenile Justice Involvement With Mental Health in Early Adulthood

Abstract: Key Points Question Is a childhood history of parental incarceration and juvenile justice involvement associated with mental health conditions in early adulthood? Findings In this nationally representative cross-sectional study, young adults with a history of both parental incarceration and juvenile justice involvement reported more mental health conditions compared with peers with no justice system exposure during childhood. Meaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Due to various moderator variables, our metaanalysis found comparable levels of heterogeneity to those in previous meta-analyses of both child welfare and juvenile justice samples [3,4]. The elevated rates of mental disorders among adults previously in out-of-home care may be explained by the use of samples in the stage of young adulthood (18-25 years) in eight studies [63,65,67,69,70,72,76,77], compared with the highest mean age of 72 years in the study sample of Fernandez et al [78]. For example, there was a variation in the age distribution (18-72 years) of samples between individual studies: as young adults may face various challenges at transition to adulthood, they might be at higher risk of mental disorders compared with older adults [30], which might mean that our estimated prevalence rates are higher than is actually the case.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Due to various moderator variables, our metaanalysis found comparable levels of heterogeneity to those in previous meta-analyses of both child welfare and juvenile justice samples [3,4]. The elevated rates of mental disorders among adults previously in out-of-home care may be explained by the use of samples in the stage of young adulthood (18-25 years) in eight studies [63,65,67,69,70,72,76,77], compared with the highest mean age of 72 years in the study sample of Fernandez et al [78]. For example, there was a variation in the age distribution (18-72 years) of samples between individual studies: as young adults may face various challenges at transition to adulthood, they might be at higher risk of mental disorders compared with older adults [30], which might mean that our estimated prevalence rates are higher than is actually the case.…”
Section: Discussionsupporting
confidence: 61%
“…For three studies, which reported gender-specific prevalence rates only [61][62][63], we calculated the combined prevalence across these subsamples in our meta-analyses [56]. We included two studies that reported only lifetime prevalence rates [48,64], because we were able to control for childhood prevalences by conducting subgroup analyses.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, weaning results in decreased feed intake, serious diarrhea, and depressed immune systems. Additionally, a number of studies have revealed that juvenile stress, such as weaning stress, has a profound impact on social behavior and metabolism in adulthood (Shtoots et al, 2018;Heard-Garris et al, 2019). For example, early life adversity (weaning stress) in piglets induces chronic functional diarrhea, intestinal permeability, and lasting alterations in gastrointestinal (GI) function (Pohl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…34,35,38 One study found that half of incarcerated youth had experienced four or more ACEs, 1441 while data from the United States and Wales suggest that greater than 90% of incarcerated adults have experienced at least one ACE, and almost 50% have experienced four or more. [1442][1443][1444] One aspect of toxic stress physiology that is of particular relevance to the justice system is the notion of stress sensitization. Individuals with a dysregulated stress response may be more sensitive to subsequent stressors in terms of risk of Sociodemographic disparities in exposure to childhood adversity are compounded by disparities in rates of referral to the criminal justice system to give rise to a chicken-egg cycle of trauma and harm in vulnerable communities.…”
Section: Primary Secondary and Tertiary Prevention Strategies In Justicementioning
confidence: 99%